PELUANG USAHA BAKED POTATO KEJU ISI DAGING DALAM PENINGKATAN NILAI TAMBAH PENJUALAN - Wijaya, Rio Richardo; Nugroho, Vidyarto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
The analysis of the business opportunity for stuffed baked potatoes with cheese and meat aims to enhance the added value of products in the food market. In a market characterized by frequent price fluctuations, innovation in food processing becomes an effective solution. The stuffed baked potato product offers a unique flavor that combines potatoes, cheese, and meat, making it appealing to consumers increasingly opting for snacks and ready-to-eat meals. The market potential for this product is significant, especially among urban populations seeking practical and delicious food options. With relatively low capital and a simple production process, this venture is accessible to various groups, including micro, small, and medium enterprises (MSMEs). Analysis indicates that the net profit from this business can be quite substantial, with a quick return on investment, making it an attractive option for prospective entrepreneurs. Effective marketing strategies using social media and creative promotions are crucial for enhancing product visibility. Additionally, diversifying flavor variants and appealing packaging will support the sustainability of the business. With support from various stakeholders, including local communities, this venture will not only provide economic benefits but also contribute to the development of a sustainable local food industry. Therefore, stuffed baked potatoes with cheese and meat hold great potential as a flagship product that can improve the welfare of entrepreneurs and attract consumer interest. ABSTRAK Analisis peluang usaha baked potato keju isi daging bertujuan untuk meningkatkan nilai tambah produk di pasar makanan. Dalam kondisi pasar yang sering mengalami fluktuasi harga, inovasi dalam pengolahan makanan menjadi solusi yang efektif. Produk baked potato keju isi daging menawarkan cita rasa unik yang menggabungkan kentang, keju, dan daging, sehingga dapat menarik perhatian konsumen yang semakin memilih makanan ringan dan siap saji. Potensi pasar untuk produk ini cukup besar, terutama di kalangan masyarakat urban yang mencari pilihan makanan praktis dan lezat. Dengan modal yang relatif kecil dan proses produksi yang sederhana, usaha ini dapat diakses oleh berbagai kalangan, termasuk pelaku usaha mikro, kecil, dan menengah (UMKM). Analisis menunjukkan bahwa keuntungan bersih yang dapat diperoleh dari usaha ini cukup signifikan, dengan waktu pengembalian modal yang cepat, menjadikannya pilihan menarik bagi calon pengusaha. Strategi pemasaran yang efektif melalui penggunaan media sosial dan promosi kreatif sangat penting untuk meningkatkan visibilitas produk. Selain itu, diversifikasi varian rasa dan kemasan yang menarik akan mendukung keberlanjutan usaha. Dengan dukungan dari berbagai pihak, termasuk komunitas lokal, usaha ini tidak hanya akan memberikan keuntungan ekonomi, tetapi juga berkontribusi pada pengembangan industri makanan lokal yang berkelanjutan. Oleh karena itu, baked potato keju isi daging memiliki potensi besar sebagai produk unggulan yang dapat meningkatkan kesejahteraan pelaku usaha dan menarik minat konsumen.